2012
DOI: 10.3390/f3030632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Small-Scale Dead Wood Additions on Beetles in Southeastern U.S. Pine Forests

Abstract: Pitfall traps were used to sample beetles (Coleoptera) in plots with or without inputs of dead loblolly pine (Pinus taeda L.) wood at four locations (Louisiana, Mississippi, North Carolina and Texas) on the coastal plain of the southeastern United States. The plots were established in 1998 and sampling took place in 1998, 1999, and 2002 (only 1998 for North Carolina). Overall, beetles were more species rich, abundant and diverse in dead wood addition plots than in reference plots. While these differences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Although declines in habitat-modifying foundation species are often associated with dramatic losses in ecosystem function and stability (Ellison et al 2005, Altieri and Witman 2006, Bracken et al 2007, Polidoro et al 2010, there is increasing evidence that some communities associated with dead foundation species can be just as diverse, if not more diverse, than those associated with live foundation species. This pattern has been documented in the mobile macroinvertebrates found in dead seagrass mattes (Borg et al 2006), diatom assemblages on dead grass stems (Grimes et al 1980), and beetle communities associated with dead pine trees (Klepzig et al 2012).…”
Section: Diversity In Light Of Foundation Species Declinementioning
confidence: 64%
“…Although declines in habitat-modifying foundation species are often associated with dramatic losses in ecosystem function and stability (Ellison et al 2005, Altieri and Witman 2006, Bracken et al 2007, Polidoro et al 2010, there is increasing evidence that some communities associated with dead foundation species can be just as diverse, if not more diverse, than those associated with live foundation species. This pattern has been documented in the mobile macroinvertebrates found in dead seagrass mattes (Borg et al 2006), diatom assemblages on dead grass stems (Grimes et al 1980), and beetle communities associated with dead pine trees (Klepzig et al 2012).…”
Section: Diversity In Light Of Foundation Species Declinementioning
confidence: 64%
“…Some studies focusing on experimentally added dead wood have found positive effects of the amount of dead wood of the same type on abundance, species number and diversity of saproxylic beetles (e.g. Klepzig et al 2012;Gossner et al 2013a). Although our gradient of dead-wood diversity comprised only four different levels, richness of saproxylic beetles responded to dead-wood diversity even when controlling for abundance ( Fig.…”
Section: E F F E C T S O F D E a D -W O O D A M O U N T A N D D E A Dmentioning
confidence: 75%
“…Dispersal limitations should not play a large role at the scale of our study (20–30 km), as the majority of saproxylic beetles and wood‐inhabiting fungi are good dispersers (Komonen & Müller, ). It is known that saproxylic beetle communities are mainly shaped by habitat filtering and dead‐wood amounts (Bouget, Larrieu, Nusillard, & Parmain, ; Gossner, Floren, Weisser, & Linsenmair, ; Heikkala et al, ; Klepzig et al, ). Therefore, within a decade, dead‐wood enrichment contributed directly to the change in community composition (see also Thorn et al, ).…”
Section: Discussionmentioning
confidence: 99%